PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, PROFITABILITAS, OPERATING LEVERAGE DAN TINGKAT PERTUMBUHAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2012 (Students' Journal of Accounting and Banking, 2014)
The purpose of this study is to examine and analyze the asset structure, size, profitability, operating leverage and growth of the capital structure in property and real estate companies in Indonesia Stock Exchange in 2010-2012.In this study, researchers obtained a sample of 37 companies during the years 2010 to 2012 so that the pool of data 111 obtained companies. But when there was outlier, the samples became 105 companies.Method samples were used in the analysis is multiple regression and analysis using SPSS for data processing.The results of this study variables asset structure is significant negative effect on the capital structure, the size is significant positive effect on capital structure. While variable profitability, operating leverage and growth had no significant effect on capital structure.Keywords: Asset Structure, Size, Profitability, Operating Leverage, Growth, Capital Structure